Cardiac involvement in hereditary myopathy with early respiratory failure: A cohort study. (6th September 2016) - Steele, Hannah E.; Harris, Elizabeth; Barresi, Rita; Marsh, Julie; Beattie, Anna; Bourke, John P.; Straub, Volker; Chinnery, Patrick F.
Abstract : Objective: To assess whether hereditary myopathy with early respiratory failure (HMERF) due to the c.951434T>C; (p.Cys31712Arg) TTN missense mutation also includes a cardiac phenotype. Method: Clinical cohort study of our HMERF cohort using ECG, 2D echocardiogram, and cross-sectional cardiac imaging with MRI or CT. Results: We studied 22 participants with the c.951434T>C; (p.Cys31712Arg) TTN missense mutation. Three were deceased. Cardiac conduction abnormalities were identified in 7/22 (32%): sustained atrioventricular tachycardia (n = 2), atrial fibrillation (n = 2), nonsustained atrial tachycardia (n = 1), premature supraventricular complexes (n = 1), and unexplained sinus bradycardia (n = 1). In addition, 4/22 (18%) had imaging evidence of otherwise unexplained cardiomyopathy. These findings are supported by histopathologic correlation suggestive of myocardial cytoskeletal remodeling. Conclusions: Coexisting cardiac and skeletal muscle involvement is not uncommon in patients with HMERF arising due to the c.951434T>C; (p.Cys31712Arg) TTN mutation. All patients with pathogenic or putative pathogenic TTN mutations should be offered periodic cardiac surveillance.